2021
DOI: 10.6007/ijarbss/v11-i9/11077
|View full text |Cite
|
Sign up to set email alerts
|

Newman’s Error Analysis of Common Errors in Solving Convergence of Power Series Using Ratio Test

Abstract: In mathematics, the students are urged to answer the questions correctly. Answers with complete sets of solutions shows a certain level of understanding of students. However, it is undeniable that some student had difficulty in answering the questions correctly. The students may not have certain understanding on a particular topic and that does not mean that they are poor in mathematics. Some errors that students do in doing mathematics may due to misunderstanding of questions, incorrect concepts, careless mis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(10 reference statements)
0
1
0
Order By: Relevance
“…From figure 6(a), (b), and (c) it is found that errors made at the process skill phase result in encoding error. Mansor et al (2021) also stated the same thing that the fourth phase, that is process skill. They stated that most students who make error in process skills tend to make error in incoding, that is the students record their result inappropriately.…”
Section: Encoding Errormentioning
confidence: 93%
“…From figure 6(a), (b), and (c) it is found that errors made at the process skill phase result in encoding error. Mansor et al (2021) also stated the same thing that the fourth phase, that is process skill. They stated that most students who make error in process skills tend to make error in incoding, that is the students record their result inappropriately.…”
Section: Encoding Errormentioning
confidence: 93%